The effect of different dosage and duration of lansoprazole-clarithromycin- amoxycillin combination on Helicobacter pylori eradication - İrfan SOYKAN and Hülya ÇETİNKAYA and Cansel TÜRKAY and Ali ÖZDEN (Turkish Journal of Gastroenterology, 2019)
-